A cheap water treatment system for Sudanese Gezira villages - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
The Sudanese authorities are now drawing plans to build a new filtration plant using broken bricks as a simple and cheap solution to the problem of providing clean water in Sudan's irrigated Gezira area. The population of this area related to the...